0378 Are People with Severe Insomnia Able to Discontinue Hypnotics after Chronic Use?. (12th April 2019) - Koshorek, Gail; Verkler, Jelena; Withrow, Dana; Roth, Thomas; Roehrs, Timothy
Abstract: Introduction: A concern among physicians prescribing hypnotics is the inability to discontinue hypnotics after chronic use. This concern has never been directly tested in a controlled prospective study. This is a report of results from an on-going "blinded" trial in which insomnia subjects are instructed to stop taking study medication after 6 months of nightly use. Methods: DSM-V diagnosed insomnia subjects, 23-61 yrs, (n=25, 21 females), with disturbed sleep (i.e. polysomnographic sleep efficiency of ≤ 85%), no other sleep disorder, unstable medical or psychiatric disorder or drug dependency completed the trial. Participants were randomized to zolpidem XR (12.5 mg), eszopiclone (3 mg) or placebo nightly for 6 months (groups A: n=10, B: n=6, C: n=9). After 6 months of nighty use, over a 2-week choice period, they were instructed to discontinue hypnotic use, but if necessary, to take either 1, 2, or 3 capsules of medication (zolpidem XR 6.25 mg, 6.25 mg, placebo; eszopiclone 2 mg, 1 mg, placebo 1, 2 and 3 respectively; or 3 placebos). Results: The number of capsules taken declined from week 1 to 2 (p< .01). Over 2 weeks 13 participants took 0 (48%), 8 ≤ 6 (32%) and 4 ≥ 10 capsules (1 each took 42, 19, 13, and 10). Among those taking capsules most took one capsule per night and 9 took > 1 capsule. Those 4 taking ≥ 10 were younger (p<.05), but did not differ in screening sleep efficiency or blinded treatment group. Importantly 1 subject took every capsule available. Conclusion: The majority (80%) of the participants discontinued 6-month nightly hypnotic use (i.e. took < 6 total capsules over 2 weeks) and among those taking capsules the rate declined from week 1 to 2. Age may help identify the few with difficulty discontinuing. Support (If Any): NIDA, grant#: R01DA038177 awarded to Dr. Roehrs